Long noncoding RNA CASC11 suppresses sorafenib-triggered ferroptosis via stabilizing SLC7A11 mRNA in hepatocellular carcinoma cells - Fei Chen; Liang Wang (Discover Oncology, 2023)
Abstract As a frontline treatment for patients with advanced hepatocellular carcinoma (HCC), sorafenib is an effective drug approved by the Food and Drug Administration (FDA). Ferroptosis, a newly defined programmed cell death process with the hallmark of the accumulation of iron-dependent lipid peroxides, can be induced by sorafenib treatment. Our previous study identified oncogenic roles of long noncoding RNA (lncRNA) Cancer susceptibility candidate 11 (CASC11) in HCC progression. However, the relationship between CASC11 and sorafenib-induced ferroptosis in HCC remains unclear. In the present study, we aim to investigate the role of CASC11 in sorafenib-induced ferroptosis in HCC cell lines and determine the involved molecular mechanisms. Here, we demonstrated that sorafenib decreased CASCL11 expression. Knockdown of CASC11 enhanced sorafenib-induced ferroptosis, while overexpression of CASC11 exerted the opposite effect in HCC cells. Moreover, CASC11 led to the accumulation of intracellular malondialdehyde (MDA), lipid reactive oxygen species (ROS) and Fe2+ while depleting glutathione (GSH), thereby suppressing sorafenib-induced ferroptosis and cell death. Ferrostatin-1 (Ferr-1), a ferroptosis inhibitor, reversed the enhanced anticancer effect of sorafenib caused by the silence of CASC11 in HCC cells. Mechanistically, CASC11 upregulated the expression of solute carrier family 7 member 11 (SLC7A11) which is critical for ferroptosis inhibition. CASC11 associated with and stabilized SLC7A11 mRNA. In summary, our data revealed, for the first time, that CASC11 inhibits the sorafenib-induced ferroptosis in HCC cells via regulating SLC7A11, providing a new basis for clinical therapeutic strategies for patients with HCC.